Epilepsy as an Autoimmune Disease - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs, 2014)
Investigators at University of New South Wales, Sydney, Australia, and Boston Children's Hospital, Harvard Medical School, conducted a retrospective population-level study of the relationship between epilepsy and 12 common autoimmune diseases: type 1 diabetes mellitus, psoriasis, rheumatoid arthritis, Graves disease, Hashimoto thyroiditis, Crohn disease, ulcerative colitis, systemic lupus erythematosus, antiphospholipid syndrome, Sjogren syndrome, myasthenia gravis, and celiac disease.